Remembering Protest in Britain since 1500 Memory, Materiality and the Landscape - Griffin, Carl J.; McDonagh, Briony (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XIV, 253 p. 6 illus. in color.